In-depth morphological study of mesiobuccal root canal systems in maxillary first molars: review - Seok-Woo Chang; Jong-Ki Lee; Yoon Lee; Kee-Yeon Kum (Korean Academy of Conservative Dentistry, 2013)
A common failure in endodontic treatment of the permanent maxillary first molars is likely to be caused by an inability to locate, clean, and obturate the second mesiobuccal (MB) canals. Because of the importance of knowledge on these additional canals, there have been numerous studies which investigated the maxillary first molar MB root canal morphology using in vivo and laboratory methods. In this article, the protocols, advantages and disadvantages of various methodologies for in-depth study of maxillary first molar MB root canal morphology were discussed. Furthermore, newly identified configuration types for the establishment of new classification system were suggested based on two image reformatting techniques of micro-computed tomography, which can be useful as a further 'Gold Standard' method for in-depth morphological study of complex root canal systems.